The Influence Of Gravity Model And Intra Industry Trade Factors On Indonesian Tourism Demand From Ten Countries - Ni Wayan Leoni Widianti; Made Heny Urmila Dewi (International Journal of Management Research and Economics, 2024)
The health emergency conditions during the Covid-19 pandemic which also had an impact on the global social and economic crisis, the tourism sector was one of the sectors most negatively affected, especially the decline in tourist visits due to the travel restriction policy. This condition also affects the contribution of the tourism sector to the national economy. This research was conducted to observe the impact of factors in the gravity model and intra-industry trade, including relative distance, GDP per capita, tourism sector integration, and exchange rates on tourism demand in Indonesia from ten countries during 2017-2022 on 60 data samples with observation techniques and panel data regression model observations. Results were obtained which stated that the relative distance variable and GDP per capita had a negative effect on Indonesian tourism demand, conversely the integration of the tourism sector had a positive effect on Indonesian tourist demand, while the exchange rate variable had no significant impact on housing tourism demand in Indonesia from ten countries in 2017-2022.